Kidney transplantation in patients with systemic sclerosis: a nationwide multicentre study. (March 2017) - Bertrand, Dominique; Dehay, Julien; Ott, Julien; Sberro, Rebecca; Brunelle, Charlotte; Kamar, Nassim; Colosio, Charlotte; Chatelet, Valérie; Albano, Laetitia; Girerd, Sophie; Audard, Vincent; Barbet, Christelle; et al.
Summary: Kidney transplantation is one of the therapeutic options for end‐stage renal disease (ESRD) in systemic sclerosis (SS). Current evidence demonstrates poorer patient and graft survival after transplantation in SS than in other primary kidney diseases. All the patients presenting ESRD associated with SS who had received a kidney allograft between 1987 and 2013 were systematically included from 20 French kidney transplantation centres. Thirty‐four patients received 36 kidney transplants during the study period. Initial kidney disease was scleroderma renal crisis in 76.4%. Extrarenal involvement of SS was generally stable, except cardiac and gastrointestinal involvements, which worsened after kidney transplantation in 45% and 26% of cases, respectively. Patient survival was 100%, 90.3% and 82.5% at 1, 3 and 5 years post‐transplant, respectively. Pulmonary involvement of SS was an independent risk factor of death after transplantation. Death‐censored graft survival was 97.2% after 1 and 3 years, and 92.8% after 5 years. Recurrence of scleroderma renal crisis was diagnosed in three cases. In our study, patient and graft survivals after kidney transplantation can be considered as excellent. On this basis, we propose that in the absence of extrarenal contraindication, SS patients presenting with ESRD should be considered for kidney transplantation.